2022
DOI: 10.1371/journal.pone.0270430
|View full text |Cite
|
Sign up to set email alerts
|

Medicalizing risk: How experts and consumers manage uncertainty in genetic health testing

Abstract: Given increased prevalence of direct-to-consumer (DTC) genetic health tests in recent years, this paper delves into discourses among researchers at professional genomics conferences and lay DTC genetic test users on popular discussion website Reddit to understand the contested value of genetic knowledge and its direct implications for health management. Harnessing ethnographic observations at five conferences and a text -analysis of 52 Reddit threads, we find both experts and lay patient-consumers navigate the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 49 publications
1
2
0
Order By: Relevance
“…They also found that clinicians providing antenatal counselling enact shared decision-making dependent on the pregnant woman's level of worry or concern about foetal abnormalites (2016). Similar co-production of decision-making was recently found in direct-to-consumer genetic counselling (Mukherjee et al, 2022). While the actual management of uncertainty is certainly more dynamic and interactive than reported by the genetic counsellors, our study showed how counsellors reported the cultivation of professional expertise across time-points and behind-the-scenes interventions that they then bring to the counselling session and which may be invisible in the actual counselling session.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…They also found that clinicians providing antenatal counselling enact shared decision-making dependent on the pregnant woman's level of worry or concern about foetal abnormalites (2016). Similar co-production of decision-making was recently found in direct-to-consumer genetic counselling (Mukherjee et al, 2022). While the actual management of uncertainty is certainly more dynamic and interactive than reported by the genetic counsellors, our study showed how counsellors reported the cultivation of professional expertise across time-points and behind-the-scenes interventions that they then bring to the counselling session and which may be invisible in the actual counselling session.…”
Section: Discussionsupporting
confidence: 78%
“…While the former consolidates their subordinate role as information purveyors, the latter indicates more ambitious professional aspirations to develop a knowledge base. Given the uneven spread of ‘personalised’ and ‘precision’ medicine, of which genomic data is a crucial constituent (Juengst et al., 2016), claiming expertise in VUS communication could strengthen the demand for the professional services of genetic counsellors in this fast‐growing new territory (Mukherjee et al., 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Reddit's popularity, as the seventh most visited website in the United States, and its emphasis on information exchange render it a notable source for interactional content analysis application (Mukherjee et al. 2022). Reddit has been shown to activate high levels of self‐disclosure by participants (Pilkington and Rominov 2017) and enables access to data that might otherwise be difficult to attain.…”
Section: Studying Gunsmentioning
confidence: 99%